CATARACT SURGERY AND INTRAOCULAR LENS POWER CALCULATION IN A PATIENT WITH ANTERIOR MEGALOPHTHALMOS WITH NORMAL SIZED CRYSTALLINE LENS; CASE REPORT - Glišić Selimir; Jovanovic Milos; Gaković Aleksandar; Dacic-Krnjaja Bojana (Sanamed, 2015)
Cataract surgery and intraocular lens power calculation is challenging in patients with anterior megalophthalmos and cataract, with postoperative refractive surprise frequently reported. Deep anterior chamber in these patients substantially influence effective lens position. To minimize possibility of refractive surprise, we used Haigis formula that takes into account anterior chamber depth in the lens power calculation for our patient. Cataract was managed by phakoemulsification with standard intraocular lens implanted in the capsular bag. Postoperatively, satisfying refractive result was achieved and refractive surprise was avoided.